A study on the effects of different microbial inoculants on the decomposition of organic waste by using semi passive aerated reactor - Kamaruddin M.A.; Norashiddin F.A.; Idrus A.F.M.; Zawawi M.H.; Alrozi R. (American Institute of Physics Inc., 2023)
Food wastes disposed at landfills can be recovered and transformed into value-added product, which helps to solve the environmental issues of solid waste. In this study, a composting method whereby food wastes are converted into compost through decomposition by inoculants. The decomposition rate of the food wastes and dried leaves was enhanced by the compost functions as fertilisers for soil and plants. The proposed modified compost bin is an effective solution to decompose the food wastes which are placed evenly alternating between the dead leaves. The inoculant was poured onto the food waste and then layered by the dead leaves. The ratio of food wastes to dead leaves is 2:1. The inoculants used were Effective Microorganisms (EM), vermitea (VCT), obsolete pasteurised milk (OPM) and the control bin without any inoculant, respectively. The temperature and pH of each compost were monitored every three to four days for 10 weeks. It was found that the EM assisted compost stabilised faster compared to the other three of the VCT, OPM and control composts. By week 7, the EM compost has achieved all the criterion to be considered as stable and matured compost whereas the VCT compost achieved all the criterion only by week 9 but the OPM assisted compost did not meet all the criterion even by week 10. In week 7, the EM assisted compost showed the temperature of 22.40.55C with pH 7.70.01. The moisture content, in the beginning, was 56% and at the end was 32% with a decreased of 24%. The C/N ratio is 12.48 and the germination test using mung beans showed that the compost has achieved 75% and is suitable to be used as fertilizer. 2018 Author(s).